Faktor-Faktor Yang Mempengaruhi Investor Berinvestasi Di Perusahaaan Bumiputera Capital Indonesia (BCI) Cabang Pontianak - Dedy Hariyanto (JURNAL MANAJEMEN MOTIVASI, 2014)
The purpose of research is to determine the factors that influence the attractiveness of investors to investin the Company Bumiputera Capital Indonesia (BCI) Pontianak branch. This study used a descriptivemethod. The population of this study is investors who invest in the Indonesian capital BumiputeraCompany (BCI), meanwhile, the sample of 100 people who have been through incidental samplingtechnique. The analysis of this research is factor analysis. The results showed that the factors consideredinvesting in the Company Bumiputera Capital Indonesia is the reliability factor (realiability) which consistsof four variables consists of precision service, company image, company performance and speed ofservice. These factors can explain the variation of the total diversity (cumulative percentage of variance)of 72.221%. That is one of the factors capable of affecting the attractiveness of investors to invest in theCompany Bumiputera Capital Indonesia at 72.221%. The variables that influence on the attraction ofinvestors to invest is a factor Offer 0.851 shares of the company and the smallest is 0.571 Transactionsthrough online system.